El proceso de lectura y su relación con los resultados de aprendizaje de lengua y literatura de la escuela de Educación Básica “Quito” en el periodo lectivo 2015-2016. Guía didáctica. - Ibarvo Arias, Deisy Andrea (2016)
This research entitled THE PROCESS OF READING AND HIS RELATIONSHIP WITH THE RESULTS OF LEARNING OF LANGUAGE AND LITERATURE OF THE SCHOOL OF EDUCATION BASIC OMNIUM PERIOD SCHOOL 2015-2016. It is a response to the process interrelated development of reader behavior whose main purpose is to define a methodology specifies in advance of reading teaching. Showed a high rate of students with poor school performance making it difficult to obtain favorable outcomes in language and literature at the time of reading the texts, presented low fluidity, without analysis or criticality in newsrooms and improper use of punctuation and reading signs, problems beset the institution and the society in general. This research presents as general objective to assess the incidence of reading process and its relationship to learning outcomes. Therefore on the findings of this thesis is planned a hypothesis como the proper process of reading in the learning outcomes in order to enhance the teaching practice in the teaching of reading and progress of the research. Is important design strategies didactic to observe, describe and explain them processes that follow them students in the compliance of the activities of the reading. Achievements to be obtained are teachers motivated by applying technical readings adapted to the body work and the application of contests and tales, speaking spelling and penmanship. Students develop habits through the mastery of skills in the reading process. Steering tracking and supporting the participation of students and with the coordination of teachers. Present in the collaboration within and outside the institution's educational interactive family parents. A proposal is developed through a didactic guide of reading practice for the students of the school of basic education "Quito" with improvements to all the difficulties raised by providing an effective advancement in the process of reading.